Analysis of Determining the Qualification/Degree of Injuries in Injury Cases Reviewed From Legal and Medical Aspects Through Focus Group Discussion - Farah Primadani Kaurow; Feny Windiyastuti; Jamiatur Robekha (Sean Institute, 2025)
The determination of the qualification/degree of injury in the injury case is crucial in the criminal justice system, because it will be used as a consideration for law enforcement officials in determining criminal sanctions against violent perpetrators. The degree of injury when viewed from legal and medical aspects has several differences. In the legal aspect, the determination of the qualification/degree of injury is based on existing legal foundations, such as the Criminal Code and specific laws in cases of violence, for example domestic violence, violence against children and traffic accidents. Meanwhile, in the medical aspect, a doctor will consider starting from diagnosis, medical therapy needs and prognosis. There is one similarity in both aspects, namely the qualification/degree of serious injury, where in both aspects the basis of the criteria in article 90 of the Criminal Code is used. However, in practice in the field, the imposition of sanctions against the perpetrators will absolutely depend on the existing legal evidence and the judge's trust. This is in accordance with what is mentioned in the Criminal Procedure Code. The research method used in this study is a normative juridical method, which is a method that is carried out based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research. This research will analyze legal issues, facts, and other legal phenomena related to the legal approach, then obtain a comprehensive picture of the problem to be researched. The assessment of the qualification/degree of injury from the legal and medical aspects uses different basis of consideration. From the legal aspect, it will be guided by the Criminal Code and specific laws depending on the case handled. From a medical aspect, it is guided by clinical/medical considerations of the effects of the injury caused on the victim's body.